2017
DOI: 10.1186/s12199-017-0654-3
|View full text |Cite
|
Sign up to set email alerts
|

The Hokkaido Birth Cohort Study on Environment and Children’s Health: cohort profile—updated 2017

Abstract: The Hokkaido Study on Environment and Children’s Health is an ongoing study consisting of two birth cohorts of different population sizes: the Sapporo cohort and the Hokkaido cohort. Our primary study goals are (1) to examine the effects of low-level environmental chemical exposures on birth outcomes, including birth defects and growth retardation; (2) to follow the development of allergies, infectious diseases, and neurobehavioral developmental disorders and perform a longitudinal observation of child develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 74 publications
2
58
0
Order By: Relevance
“…Several important potential covariates, including smoking, fish intake and environmental contaminants such as PFOS and mercury were considered. Our previous reports on the same cohort showed that PFOA, Mono-2-ethylhexyl phthalate, Bisphenol A are not associated with maternal or neonatal TH levels (Kato et al, 2016;Minatoya et al, 2016;Minatoya et al, 2017).…”
Section: Strengths and Limitationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Several important potential covariates, including smoking, fish intake and environmental contaminants such as PFOS and mercury were considered. Our previous reports on the same cohort showed that PFOA, Mono-2-ethylhexyl phthalate, Bisphenol A are not associated with maternal or neonatal TH levels (Kato et al, 2016;Minatoya et al, 2016;Minatoya et al, 2017).…”
Section: Strengths and Limitationsmentioning
confidence: 89%
“…Details of the study have been described previously (Kishi et al, 2017;Kishi et al, 2013;Kishi et al, 2011) The study design was approved by the ethics committee of Hokkaido University Graduate School of Medicine. The study protocol conformed to the ethical rules of the Japanese government.…”
Section: Study Populationmentioning
confidence: 99%
“…This study formed as a follow-up study of a prospective birth cohort study, the Hokkaido Study on Environment and Children’s Health. The details of cohort profile can be found elsewhere [ 26 , 27 ]. In the Hokkaido Study, we established sub-cohort population and how we set it up was described as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Perinatal data, such as the infant's birthweight and sex, were obtained from birth records maintained by an obstetrician. [20][21][22] This cohort consisted of 20 926 pregnant women, but only the 4,851 children born between April 2008 and November 2011 were included in this study. When they turned 5 years old, we sent follow-up questionnaires to their parents.…”
Section: Study Participantsmentioning
confidence: 99%